Performance of Modified Pneumonia Severity Indexes in Community-Acquired Pneumonia - Yasemin Yılmaz; Aynur Yurtseven (Eurasian Journal of Emergency Medicine, 2025)
Aim: In patients with community-acquired pneumonia, we observed that the impact of the age variable commonly used in Pneumonia Severity scores to predict mortality risk is disproportionate within the pneumonia severity index (PSI). In this context, our study aimed to evaluate and compare the effectiveness of pneumonia severity scores, adjusted for demographic factors such as age and gender, in predicting intensive care unit (ICU) admission and mortality, compared to PSI and CURB-65. Materials and Methods: In 2019, data on patients diagnosed with pneumonia in the emergency department were obtained through a retrospective review. The CURB-65, PSI, age-modified PSI (mPSI), and gender- modified PSI (gmPSI) scores were calculated. The predictive performance of these scores for ICU admission and mortality was statistically analyzed. Results: A total of 363 patients were included in the study, of whom 205 (56.4%) were male. Additionally, comparisons of the newly developed age-mPSI and gmPSI with the standard PSI and CURB-65 demonstrated no statistically significant difference in predicting 30-day mortality or ICU admission rates (p>0.05). Conclusion: The findings of this study indicate that the newly developed mPSI and gmPSI scoring systems yield results comparable to those of the standard PSI scoring system.